Uwarunkowania wyposażenia i zapotrzebowania gospodarstw chłopskich na dobra trwałe konsumpcyjne oraz ich znaczenie w motywacji produkcji - Dietl, Jerzy; Gregor, Bogdan (Wydział Prawa i Administracji UAM, 1987)
It is a fragment of wider studies concerning adaptation processes of private farms in conditions of the centrally planned economy in economics of shortage. The studies were conducted by means of a questionnaire interview among 965 farms in three regions of Poland characterized with different levels of agricultural production development. The sample was drawn from each one of the eight farm-size brackets separately in particular microregions. There were taken into account interrelationships between the equipment and demand for 12 durable consumer goods approached in terms of the number of possessed durable goods and separately in terms of value expressed synthetically, on the one hand, and 24 variables, on the other hand. The questionnaires were also to provide information about the place of dwelling (region and village), demographic structure of the family, characteristics of a farm, its connections with the market, and propensity of the farmer to expand production. 21 of the variables revealed a very highly significant statistical correlation with the analyzed phenomena and one variable a highly significant correlation. Apart from the significance level there were applied statistical tests in the form of corrected C. Pearson's coefficient and variance ratio test F. The studies indicate, among others, that equipment of farms with consumer durables and possibilities of satisfying demand for these goods constitute a significant motivation for production. The size and equipment of a farm with production factors, its self-dependence and propensity to expand production are interrelated with its equipment with consumer durables and with its demand. Differences among farms with regard to their equipment with these goods tend to grow.
Determinants of equipment and demand of private farms for consumer durables and their significance in motivation of production